Software distribution to remote locations - Silva, L. F. da.; Brito e Abreu, F. (EuroPLoP '10: Proceedings of the 15th European Conference on Pattern Languages of Programs, 2010)
The design of Information Technology (IT) infrastructures is a complex task since it implies a level of expertise in several areas, which rarely reside in a single person. The use of IT infrastructure patterns can improve this design process by allowing to reuse proven solutions to recurrent problems and by facilitating communication among IT design stakeholders. However, existing guidelines for designing IT infrastructures are, in most cases, presented as proprietary blueprints. As such, they are not very helpful in comparing alternatives and supporting independent design decisions. This paper introduces an example of a design pattern in the domain of IT infrastructures, covering aspects from its rationale to instantiation. This is the first step in the creation of a pattern language that will hopefully leverage the IT infrastructure design process.